Adaptation of Ukrainian legislation to european one in the field of quality management by underground water - Бойко, І. А. (Scientific Progress & Innovations, 2012)
The comparatively-legal analysis of legislation of European Union (farther - EU) and Ukraine in concerning realization of the principle of sustainable development in the process of quality management of drinking-water and protection of underground water resources.has been carried out. The process of formation, modern state and progress of regulation of legal relationships in the management by groundwater have been shown. Certain aspects that must be taken into account in the process of perfection of control system by water resourceshave been defined; recommendations on harmonization of legislation of Ukraine in the field of groundwater with the EU are given.